Comprehensive energy consumption evaluation of a dry roots vacuum Pump: An experimental, dynamic and FEM research - Chongzhou Sun; Zhilong He; Dantong Li; Wei Liu; Xiaoqian Chen; Manguo Yan (Case Studies in Thermal Engineering)
The dry Roots vacuum pump (DRVP) is widely used in vacuum applications for its large pumping speed and high reliability. This paper proposed a simulation route to comprehensively evaluate its performance and energy consumption distribution characteristics under varying conditions. First, based on dynamic modeling, the variations in motor torque, gas torque, and mechanical losses were simulated. Then, through the motor's FEM simulation, the PMSM's magnetic flux density and loss distributions, and its performance maps were obtained. Finally, further evaluations of energy consumption and performance for the entire DRVP machine were conducted by comprehensively considering the losses of both the motor and its main body. These models were well-validated by experimental results. The dynamic results indicated that the total friction torque was minimal, but became the dominant resistance component when the DRVP operated under conditions below 10 Pa inlet pressure. The FEM results showed under 6500 r·min−1 rated conditions, losses of the PMSM, including the iron, copper, eddy current, wind friction, and stray losses were measured as 0.358 kW, 0.111 kW, 0.029 kW, 0.009 kW, and 0.092 kW, respectively. Furthermore, under the operating condition of 6.622Pa inlet pressure and 4500 r·min−1 rotational speed, the motor loss, friction loss, gas compression work, and gear transmission loss accounted for 47.3 %, 37 %, 10.8 %, and 0.5 %, respectively. This research offers valuable suggestions and guidance for further energy consumption reduction and motor selection optimization in vacuum pumps.